COMPARISON OF ANTIPLATELET EFFECT AND SAFETY OF ORIGINAL DRUG «ASPIRIN CARDIO» AND GENERIC«ACECARDOL» IN PATIENTS WITH ARTERIAL HYPERTENSION 1-2 GRADE - N. A. Belolipetskiy; S. N. Tolpygina; O. А. Litinskaya; V. G. Belolipetskaya; S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии)
Aim. To compare antiplatelet effect of two acetylsalicylic acid medicines, Acecardol ("Synthesis Co. Ltd", Russia) and Aspirin cardio («Bayer AG», Germany), in patients with arterial hypertension (AH) 1-2 stage with increased risk of cardiovascular events.Material and methods. The study was double-blind, randomized, cross-over one. 32 hypertensive patients (12 men and 20 women) aged 59,4±14,4 y.o. were included in the study. They took investigated ASA medicines one after another during 4 weeks each. Antiplatelet efficacy of ASA medicines were estimated by effects on spontaneous and ADP-induced platelet aggregation at every visit.Results. 4-week therapy with both ASA medicines did not have significant effects on spontaneous platelet aggregation and the aggregation induced with low ADP concentrations (0,5 and 1,0 µM). However platelet aggregation induced with ADP in concentration of 2 µM was significantly reduced by therapies. There were not significant inter-group differences.Conclusion. ASA generic medicine Acecardol ("Synthesis Co.Ltd.", Russia) and original medicine Aspirin cardio («Bayer AG», Germany) are equivalent on antiplatelet effect.